Seminar Research on Uniformity. - Rappaport, Alfred (The Accounting Review, 1965)
Abstract This overview was prepared for students enrolled in the Graduate Seminar in Accounting Theory at Tulane University, New Orleans, Louisiana, in the Fall semester of 1964. It includes, (1) a point of view on the uniformity problem, (2) the course of research recommended to the seminar participants, and (3) an annotated bibliography arranged chronologically. Perhaps other instructors will find it helpful in discussing this urgent and complex problem. During the past few years, there has been a resurging interest in promulgating a well-conceived, authoritative set of accounting principles for business enterprises. The American Institute's current research program and the establishment of the U.S. Accounting Principles Board are promising steps toward the eventual realization of this worthy and, therefore, elusive goal. The stated purpose of the Institute's research program is to determine appropriate practice and to narrow the areas of difference and inconsistency in practice. Indeed, it would be difficult for any accountant to deny the merits of this objective. However, some very serious obstacles deter its effective implementation.